Influence of polyethylene microplastics on Brassica rapa: Toxicity mechanism investigation - Hao Wu; Beibei He; Bocheng Chen; An Liu (Emerging Contaminants, 2024)
Polyethylene microplastics (PE-MPs) have toxicity to ecological environment, including animals and plants. This study investigated the toxicity of photodegraded PE-MPs on Brassica rapa, which is a typical model plant and only have around a 30-day life cycle. It is noted that the presence of photodegraded PE-MPs inhibited Brassica rapa growth since the stem length decreased by 11.94%–51.11 % while the fresh weight and dry weight decreased by 18.56%–27.46 % and 1.90 %–6.91 % respectively, compared to the blank group. PE-MPs receiving more light radiation became more hydrophobic. This inhibited PE-MPs entering the plant body along with the process of plant absorbing water. Furthermore, when PE-MPs were located in the lower soil layers, Brassica rapa reaching them needs a longer time, hence showing lower toxicity effect than the case of PE-MPs located in the upper soil layer. The research outcomes also indicated that malondialdehyde (MDA) contents in photodegraded PE-MPs exposure group increased by 1.37%–7.28 % while the catalase activity (CAT) increased by 60.11 %. This means that PE-MPs caused oxidative stress response in plants, inducing plants to resist external stress. Transcriptomic analysis results showed that Brassica rapa, which was affected by PE-MPs, significantly up-regulated genes related to the plant-pathogen interaction pathway while the ribosome pathway genes were significantly down-regulated. This led to a decrease in growth rate and a decrease in the homeostatic level of the ribosomal subunit and hence resulting in abnormal leaf vein development. These conclusions indicated the toxic effect and damage mechanism of photodegraded PE-MPs on Brassica rapa. The novelty of this study was to use both univariate analysis and transcriptomic analysis to investigate how photodegraded PE-MPs exert toxicity on Brassica rapa. The results can provide a theoretical basis for revealing the influence of MPs on plant growth.